Pendampingan Strategi Optimalisasi Instagram sebagai Media Branding dan Promosi pada Maka Coffee - Tri Wahyu Septyani; Andi Indra Saputra Alamsyah; Risnawati Risnawati; Kurniati Asmar; Maududi Lamparawi Magenda (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to optimize the use of Instagram as a branding and promotional medium for Maka Coffee, a micro, small, and medium enterprise (MSME) in Makassar City. The primary issue faced by the partner is the suboptimal management of its Instagram account, particularly in terms of bio optimization, visual content consistency, and customer engagement. The method employed is participatory mentoring, consisting of preparation, implementation, and evaluation stages. The results indicate improvements in the quality of the account profile, which has become more informative, more consistent and structured visual content, and increased digital interaction. Quantitatively, the number of followers increased by 35.7%, while reel content views showed a significant rise, reaching up to 123 thousand views. These findings demonstrate that optimizing Instagram-based digital marketing strategies is effective in enhancing the visibility and competitiveness of MSMEs.